Deriving longer-term inflation expectations and inflation risk premium measures for Canada - Bruno Fenou; Zabi Tarshi (Bank of Canada, 2024)
We present two models for long-term inflation expectations and inflation risk premiums for Canada. First, we estimate inflation expectations using a vector autoregressive model based on the relationship of inflation with both the unemployment gap and the term structure of the Government of Canada nominal bond yields. Then we estimate the inflation risk premium by regressing the nominal term premium on a set of inflation risk factors. We find that our modelimplied measure of inflation expectations generally follows a trend similar to that of breakeven inflation rates. We also find that the estimated inflation risk premium is negative or near zero through most of the sample period because most of this period was dominated by low inflation and low growth, with investors concerned about deflation. However, the modelimplied inflation risk premium becomes positive in 2021. Because real return bonds will eventually disappear in Canada, a market-derived indicator for long-term inflation expectations is particularly relevant for central bankers. Similarly, capturing the individual components of the nominal term premium can be highly useful from a policy perspective.
Keywords: C58; E43; E47; G12; 330; Econometric and statistical methods